Геодинамические особенности зоны сочленения Евразийской плиты и Альпийско-Гималайского пояса в пределах Украины и прилегающих территорий - Гинтов, О.Б.; Егорова, Т.П.; Цветкова, Т.А.; Бугаенко, И.В.; Муровская, А.В. (Геофизический журнал, 2014)
Based on the analysis of geophysical and geological data of recent 10 —15 years the boundaries and inner structure of the transition zone from the Eurasian plate (EAP) to the Alpine-Himalayan folded belt (AHB) extending from the Eastern Carpathians to the Great Caucasus were defined here. DSS (deep seismic sounding) data of the International projects EUROBRIDGE, DOBRE, CELEBRATION 2000 and the results of reinterpretation of earlier DSS profiles along the Black Sea region were used. Results of seismic tomography studies, fulfilled by the Institute of Geophysics of NAS of Ukraine within the Eurasian part of the study area, were geologically reinterpreted. Paleogeodynamic studies and paleogeographic reconstructions, performed by the Western, Ukrainian and Russian scientists, were also involved. It is shown that velocity and density characteristics of the EAP and AHB lithosphere, that is their buoyancy, do not contradict the possibility of subduction of lithospheric plates under the EAP as well as under the AHB. In the upper mantle the sloping layers 150—200 km thick and 200—750 km long were revealed, corresponding to the areas of lithospheric plates (slabs), being submerged into the asthenosphere during different time, since the Permian-Triassic period. Almost everywhere the beginning of these slabs at the surface coincides with known and supposed, according to geological data, suture zones. Due to divergent and convergent processes, the junction zone of the EAP and AHB in the south changed its position within the band (on modern geographical basis) from the Northern Donbas to the middle part of the Black Sea basin. It has been geophysically proved that the Scythian and Rava-Russian epiorogenic zones were formed as parts of the EAP, though later they were separated from it.